2019
DOI: 10.1016/j.jtho.2019.08.424
|View full text |Cite
|
Sign up to set email alerts
|

OA04.02 CheckMate 817: First-Line Nivolumab + Ipilimumab in Patients with ECOG PS 2 and Other Special Populations with Advanced NSCLC

Abstract: Among 157 patients treated with ICIs, 65 (41.4%) experienced at least one irAE. Median time to the first irAE onset was 28 days (IQR:15-56). Baseline clinicopathologic characteristics were well balanced between patients who developed irAEs and those who did not. Median tumor mutational burden (TMB) was significantly higher among patients with irAEs compared to those without (14.4 vs 8.4 mutations/megabase [mut/Mb], P <0.01). Patients who developed at least one irAE had a significantly higher objective response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…As in the recent PePS2 trial, Checkmate 171 and Checkmate 817, we see that some patients with PS2 do appear to benefit from checkpoint inhibitors [9,26]. The PePS2 trial prospectively collected safety and efficacy outcomes on 60 NSCLC patients with PS2 treated with single agent pembrolizumab [10].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As in the recent PePS2 trial, Checkmate 171 and Checkmate 817, we see that some patients with PS2 do appear to benefit from checkpoint inhibitors [9,26]. The PePS2 trial prospectively collected safety and efficacy outcomes on 60 NSCLC patients with PS2 treated with single agent pembrolizumab [10].…”
Section: Discussionmentioning
confidence: 87%
“…The Checkmate 817 trial evaluated the role of combined nivolumab and ipilimumab, an anti-CTLA4, in special populations of NSCLC patients, including those with PS2 [26]. While the treatment-related adverse events were not increased compared to patients with a PS of 0-1, the efficacy was lower among patients with PS2, with a 19% overall response rate (ORR) and 3.6 months median progression-free survival (PFS), compared to a 36% and 5.8 months, respectively, among fitter patients.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies will hopefully help define the best initial treatment approach for this vulnerable population. Preliminary data from CheckMate 817 of first-line ipilimumab plus nivolumab in patients with either an ECOG PS 2 or with a comorbidity (such as asymptomatic untreated brain metastases, hepatic or renal impairment, HIV) 18 showed a promising mPFS of 9.6 months in patients with PD-L1 TPS ≥50% (n=33). Another prospective study (eNERGY, NCT03351361) will compare first-line ipilimumab plus nivolumab with carboplatin-based doublet chemotherapy in patients with an ECOG PS 2.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, clinical trial data to support the use of ICIs in patients with NSCLC who have impaired PS (≥2) are limited, despite an estimated prevalence of PS ≥2 among newly diagnosed adults with lung cancer of approximately 34% . One single‐arm, nonrandomized, prospective study (Checkmate 817 [An Investigational Immuno‐therapy Study for Safety of Nivolumab in Combination With Ipilimumab to Treat Advanced Cancers; clinicaltrials.gov identifier NCT02869789]) of patients with advanced lung cancer who were treated with combination nivolumab and ipilimumab showed comparable rates of toxicity among patients who had an ECOG PS 2 or significant comorbidities relative to those who had PS 0 or 1 . An additional prospective, nonrandomized study of 62 patients with advanced NSCLC and PS 2 who received with pembrolizumab reported grade 3 or 4 immune‐related adverse events in 8% and an objective response rate of 30% .…”
Section: Introductionmentioning
confidence: 99%